8. Post-Production Aspects in Performative Photography - Teodorescu Bogdan (Sciendo, 2023)
Appropriation is one of the determining concepts of the post-productive theory, denoting the choice of an object and its use or modification according to a specific intention. Operating in an index of famous images from universal art, the photographer artist calls upon the performative strategies of the environment to structure behavioral positionings observed in social space. The series of examples accesses a segment of these artistic practices in which the biblical icon plays the role of the symbolic reference, but especially of the pretextual condition within the author's conceptual construction.